An analysis of eco-innovation capabilities among small and medium enterprises in Malaysia - Najahul Kamilah Aminy Sukri; Siti Nur `Atikah Zulkiffli; Nik Hazimah Nik Mat; Khatijah Omar; Mukhammad Kholid Mawardi; Nur Farah Zafira Zaidi (Administrative Sciences, 2023)
The objective of this study is to look at how Malaysian small and medium enterprises (SMEs) are applying eco-innovation capabilities in order to sustain their business performance. Eco-innovation capabilities are represented in this study by five different types of practices, with the indication of unexpected circumstances: eco-product innovation, eco-process innovation, eco-organisational innovation, eco-marketing innovation, and eco-technology innovation. The qualitative research approach was used in the study, and the content analysis was based on in-depth interviews with six top-level managers/owners of Malaysian manufacturing SMEs. According to the data, more than half of SMEs acquired eco-innovation capabilities in order to continue their business performance and thrive in the business sector, while having to confront certain hurdles due to unforeseen situations. According to the findings, eco-innovation capabilities encourage SMEs to engage in waste management, recycling or reusing resources, research and development, sustainable goods that utilize customer requests, and the use of environment management machines. Thus, the findings of this study may aid the efforts of government agencies, policymakers, and top-tier manufacturing SMEs in building an exceptional innovation platform on which SMEs may rely for assistance and support in preserving their business performance in the future and beyond.
Keywords: 350; business performance; eco-innovation capabilities; Malaysia; small and medium-sized enterprise; sustainability